Pendekatan Manajemen Strategi Berbasis Syariah: Antara Etika, Efisiensi, dan Keunggulan Kompetitif - Sari, Meliana; Ismawati, Ismawati; Aminah, Siti; Pertiwi, Audi Auliya; Mutia, Agustina (TSAQOFAH, 2025)
The conventional strategic management approach often overlooks ethical and spiritual dimensions, despite the increasing complexity of global challenges that necessitate the integration of such values. This study aims to analyze the application of Sharia-based strategic management in organizations or companies to establish an efficient, competitive managerial system grounded in Islamic ethical principles such as ʿadl (justice), ṣidq (truthfulness), amānah (trustworthiness), and iḥsān (excellence). The methodology includes literature review, a qualitative approach, and case studies with normative analysis of scholarly literature, fatwas, trade contracts, and online business practices. The main findings indicate that Sharia-based strategic management can achieve a balance between operational efficiency and competitive advantage while maintaining spiritual and social values. Three key pillars were identified: ethics as the foundation of strategy, efficiency in resource management aligned with the prohibition of isrāf (wastefulness), and the pursuit of long-term, value-driven competitive advantage. This study concludes that the model is not only applicable to Islamic organizations but also holds potential as a universal framework for sustainable modern managerial practices. The findings offer both conceptual and practical contributions to the development of management systems that integrate religious values with contemporary business goals.